Two new species of stoneflies (Plecoptera: Nemouridae) from Northeastern India, with a checklist of the family in the Indian Subcontinent - Murányi, Dávid; Li, Weihai (Zootaxa, 2013)
A new species of the genus Amphinemura (Plecoptera: Nemouridae: Amphinemurinae), A. baumanni sp. n. is described on the basis of five males collected in the Darjeeling District of West Bengal, India. A new species of the genus Sphaeronemoura (Amphinemurinae), S. siveci sp. n. is described on the basis of a single male collected in the West Garo Hills District of Meghalaya, India. A checklist of the family Nemouridae from the Indian Subcontinent is given with zoogeographical comments.